2018
DOI: 10.1016/j.jclepro.2017.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the economic impacts of heat waves: A case study of Nanjing, China

Abstract: The southeast region of China is frequently affected by summer heat waves. Nanjing, a metropolitan city in Jiangsu Province, China, experienced an extreme 14-day heat wave in 2013. Extreme heat can not only induce health outcomes in terms of excess mortality and morbidity (hospital admissions) but can also cause productivity losses for self-paced indoor workers and capacity losses for outdoor workers due to occupational safety requirements. All of these effects can be translated into productive working time lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 24 publications
(28 reference statements)
2
60
0
1
Order By: Relevance
“…In this work, all-cause mortality, hospital admissions and emergency visits of heat-related illness (such as heat stroke and heat exhaustion) are used in view of their different considerations in evaluating proper thresholds of the heat warning system. A warning system with the threshold identified using all-cause mortality aims at reducing overall mortality, while those with thresholds determined using hospital admissions and emergency visits target at reducing morbidity related to work productivity and/or human wellbeing (Xia et al, 2018). In reality, some countries may only have complete datasets for one of the health records presented here.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, all-cause mortality, hospital admissions and emergency visits of heat-related illness (such as heat stroke and heat exhaustion) are used in view of their different considerations in evaluating proper thresholds of the heat warning system. A warning system with the threshold identified using all-cause mortality aims at reducing overall mortality, while those with thresholds determined using hospital admissions and emergency visits target at reducing morbidity related to work productivity and/or human wellbeing (Xia et al, 2018). In reality, some countries may only have complete datasets for one of the health records presented here.…”
Section: Introductionmentioning
confidence: 99%
“…Although these databases have helped gain a comprehensive understanding of regional disparities and spillover effects in interregional and international trade, none of current MRIOs (national or provincial) offer insights in assessment at the local scale, particularly at the city level. This widens a massive gap between research resolution and government decision making, especially in the context of increasing significance of cities with regard to economic growth, energy consumption, resources management, and public health (Nair, George, Malano, Arora, & Nawarathna, ; Shan et al., ; Xia et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Related studies use long-term observed temperature data from meteorological stations to explore the geographical patterns and temporal variations of extreme heat events at the national or regional level in China [26][27][28]. The second is assessing the impacts and potential risks of extreme heat on human health [29][30][31][32], agricultural production [33,34], economic development [7], psychological perception [35], etc. The third is constructing heat vulnerability index or heat risk index by integrating hazard, exposure, sensitivity, and adaptive capacity to assess extreme heat risk at urban or regional level [36][37][38].…”
mentioning
confidence: 99%